2021
DOI: 10.3390/brainsci11040472
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Spinal Cord Stimulation Enhances Walking Performance and Reduces Spasticity in Individuals with Multiple Sclerosis

Abstract: Gait dysfunction and spasticity are common debilitating consequences of multiple sclerosis (MS). Improvements of these motor impairments by lumbar transcutaneous spinal cord stimulation (tSCS) have been demonstrated in spinal cord injury. Here, we explored for the first time the motor effects of lumbar tSCS applied at 50 Hz for 30 min in 16 individuals with MS and investigated their temporal persistence post-intervention. We used a comprehensive protocol assessing walking ability, different presentations of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 108 publications
(70 reference statements)
1
31
0
Order By: Relevance
“…Similarly, cervical epidural SCS has been used for promoting volitional hand function in individuals with chronic tetraplegia [5]. Consistent with epidural SCS approaches, noninvasive transcutaneous spinal cord stimulation (tSCS) has also been utilized successfully in applications for improving sensory and motor function during lower-limb voluntary movement [6] and walking using lumbar stimulation [7][8][9][10][11][12], trunk stability and standing with lower thoracic and lumbar stimulation [13,14], and gripping and upper-limb function with cervical stimulation [15][16][17][18][19]. Computer simulations and experimental studies using animal models as well as human studies have shown compelling evidence that electric impulses induced by either implanted epidural or surface non-invasive electrodes can primarily activate the afferent fibers in the posterior roots of the spinal cord [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cervical epidural SCS has been used for promoting volitional hand function in individuals with chronic tetraplegia [5]. Consistent with epidural SCS approaches, noninvasive transcutaneous spinal cord stimulation (tSCS) has also been utilized successfully in applications for improving sensory and motor function during lower-limb voluntary movement [6] and walking using lumbar stimulation [7][8][9][10][11][12], trunk stability and standing with lower thoracic and lumbar stimulation [13,14], and gripping and upper-limb function with cervical stimulation [15][16][17][18][19]. Computer simulations and experimental studies using animal models as well as human studies have shown compelling evidence that electric impulses induced by either implanted epidural or surface non-invasive electrodes can primarily activate the afferent fibers in the posterior roots of the spinal cord [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of walking in humans, lumbar tSCS applications for modulation of spinal locomotor circuits have been the main focus of many previous studies [7][8][9][10][11][12]. Although cervical tSCS is also expected to have similar neuromodulatory effects on the upper-limb muscle function, it has been unexplored relative to lumbar tSCS application until recently.…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous SCS uses surface electrodes placed on the paravertebral and abdominal skin to generate a current flow through the lower trunk, partially crossing the dural sac [5,17] (see Figure 1). Independent studies have shown the efficacy of tSCS to ameliorate spasticity and augment voluntary motor control, including locomotion in individuals with SCI [18][19][20][21][22][23][24] as well as multiple sclerosis [25,26]. As a clinically accessible and noninvasive approach, tSCS was suggested to hold the potential to develop into a widely used neurorehabilitation technique and to serve as a screening tool to estimate individually attainable therapeutic outcomes of EES [23].…”
Section: Introductionmentioning
confidence: 99%
“…The concomitant activation of anterior root efferents would lead to direct M wave-like responses superimposed on the EMG signals of the PRM reflexes, owing to their similar onset latencies [ 1 , 2 , 35 ]. In interventional studies using tonic transcutaneous spinal cord stimulation [ 10 , 11 , 13 , 38 , 39 , 40 , 41 , 42 , 43 ], electrical activation of anterior roots would bypass the target spinal circuits and generate continuous contractions of the respectively innervated lower-limb muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Trains of stimuli can therefore provide tonic multisegmental afferent input to the spinal cord, comparable with epidural spinal cord stimulation [ 6 ]. As a result, transcutaneous lumbar spinal cord stimulation has been used for neurophysiological studies by investigating reflex modulation in multiple lower limb muscles simultaneously [ 7 , 8 , 9 ] as well as for neuromodulation of sensorimotor function after spinal cord injury [ 10 , 11 , 12 ] and multiple sclerosis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%